Application of Pamsimas for Village Communities in the Perspective of Maqashid Sharia (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Water and sanitation are important infrastructure sectors to improve public health. The problem of the availability of clean water and the decrease in the degree of the environmental health of people in rural areas is serious, so the Pamsimas program is needed. The method used in this research is descriptive qualitative with the interview, observation, and documentation techniques as a data collection tool. This study also used sharia maqashid analysis. It can be concluded that applying for the Pamsimas program in Baleraksa Village is in accordance with maqashid sharia. This can be seen in terms of providing social and home connections, changes in clean and healthy living behavior, quality water sources, installation of healthy latrines, harmonious understanding in protecting and conserving existing raw water, not exploiting water sources excessively, its management also contributes to the village government and the community. In addition, its management is building waterways and other impacts on improving the economy, social and environmental sustainability